Core curriculum in cariology for dentistry degrees in the Republic of Argentina - Carletto Körber, Fabiana PM (2023)
Aim: To prepare a consensus document of the cariology contents and competences included in the curriculum for the dentistry degree at Argentine dental faculties/schools. Materials and Method: Planning the process in stages: Stage 1- Diagnosis of the situation (Google Form) and invitation to participate extended to the 20 academic units (AU) that offer dentistry degrees. Stage 2- Assessment process of Content (C) and Competences (I) agreements in the five domains: D1 Basic Sciences, D2 Risk and diagnosis of dental caries, D3 Decision-making for non-invasive treatments, D4 Decision-making for invasive treatment, and D5 Evidence-based cariology at community level. Stage 3- Consensus. Stages 2 and 3 were held in Workshop format in virtual mode (W). Results: Stage 1- Of the total 20 Google forms sent to the AU, 13 responses were received: 7 from National Universities and 6 from Private Universities. All participants agreed to be part of the consensus. Stage 2- W: 20 representatives from 10 AU participated. It began with a contextualizing conference, after which the representatives were divided into 5 groups to assess the agreements of each D. Stage 3- The Cariology Curriculum document was organized into 5 Domains, and 23 C and 31 I of clinical application were defined for teaching cariology. The contents and competences for each domain were agreed upon. The final document was sent to all W participants for their approval and dissemination in each AU involved. Conclusion: Cariology contents were defined for dentistry students at Universities in the Argentine Republic.